The effect of a top gate voltage on the Quantum Hall measurement of a 2DEG InGaAs/InAlAs hetero-structure - Maguim, Silatsa Carine (Department of Physics, 2023)
The main purpose of this thesis is to investigate the quantization of the Hall resistance "Rxy " as well as the Shubnikov De Haas oscillations of the longitudinal "Rxx " resistance in a two dimensional electron system at different gate voltages. The sample measured utilised the InGaAs/InAlAs heterostructure grown via Molecular Beam Epitaxy (MBE). The above-mentioned effects are investigated before and after exposure of the sample to UV light. To calculate the electron density and mobility of the sample on each gate voltage, two different methods are used. The Fast Fourier transform method and the minima method. The results show that illumination increase the electron density and mobility of the sample. Results further show that both methods found similar results. Another remarkable observation is that the as gate voltage becomes more negative the density of electrons decreases and so the mobility. The maximum electron density using the FFT method is 1.8560 1011cm−2 with the mobility of 363880cm2V −1 s −1 . This results fall within the standard errors calculated by the minima method and given by: 1.7889 ± 0.026727 1011cm−2 with a mobility of 378340cm2V −1 s −1 .